2023
DOI: 10.3390/agriculture13091684
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Toxic Elements: A Review on Their Soil Behavior and Plant Attenuation Mechanisms against Their Toxicity

Georgios Thalassinos,
Spyridon A. Petropoulos,
Aspasia Grammenou
et al.

Abstract: The presence of potentially toxic elements (PTEs) can induce phytotoxicity and growth inhibition in plants. These elements are bioaccumulated and biomagnified in the food chain due to their high stability and resistance to biodegradation. The availability and mobility of PTEs in soil depend on certain physicochemical procedures. Many scientific studies on PTEs have provided valuable information about the processes, environmental fate, effects and remediation techniques. However, there is a need for gathering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 113 publications
0
4
0
Order By: Relevance
“…Also, Zn was found in compost (203 mg kg −1 ) and frass (70 mg kg −1 )-the four treatments of which (compost and frass at 2% and 4%) were found with increased Zn extractability. Although added Pb and Zn concentrations were low compared to the very high initial contents in soil, it is known that newly introduced metals are much more mobile than those deposited in soils over long periods of time [61]. Thus, these impurities may have caused the recorded increased DTPA extractability of Pb and Zn.…”
Section: Discussionmentioning
confidence: 95%
“…Also, Zn was found in compost (203 mg kg −1 ) and frass (70 mg kg −1 )-the four treatments of which (compost and frass at 2% and 4%) were found with increased Zn extractability. Although added Pb and Zn concentrations were low compared to the very high initial contents in soil, it is known that newly introduced metals are much more mobile than those deposited in soils over long periods of time [61]. Thus, these impurities may have caused the recorded increased DTPA extractability of Pb and Zn.…”
Section: Discussionmentioning
confidence: 95%
“…At low concentrations, these PTEs can help some cellular functions in plants, as well as pigment biosynthesis, enzyme activities, photosynthesis, sugar metabolism, respiration, nitrogen fixation, and other functions, but even these elements become toxic at increased concentrations, affecting plant growth (Rashid et al 2023 ). Other PTEs such as Cd, Pb, As, Hg, and Sb are non-essential and highly toxic even at low concentrations and affect biota, and finally human health (Briffa et al 2020 ; Senila et al 2022 ; Thalassinos et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Soil deterioration due to the accumulation of potentially toxic elements (PTEs) is a threat to both crop production and the environment [1,2], while PTEs have become a great concern to food security and human health due to their high toxicity, stability, and non-biodegradability [3][4][5]. Among these PTEs, cadmium (Cd) is one of the most important pollutants, being a hazardous and carcinogenic element even at low concentrations [6].…”
Section: Introductionmentioning
confidence: 99%
“…These organic substances may alleviate the mobility of PTEs by forming chelating bonds and stable organometallic complexes with metallic ions in mineral structures, thereby mitigating accumulation by plants and transfer in the trophic chain [19]. Usage of HMWOAs has been reported to minimize the total concentrations of Pb and Cd [3]. However, Evangelou et al [28] indicated the use of humic acids as an alternative chelating agent, as they can increase the solubility of cationic metals and absorption by roots.…”
Section: Introductionmentioning
confidence: 99%